2021
DOI: 10.1136/ebmental-2021-300277
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood mental disorders in high-income countries: a systematic review and meta-analysis to inform policymaking

Abstract: QuestionMental disorders typically start in childhood and persist, causing high individual and collective burdens. To inform policymaking to address children’s mental health in high-income countries we aimed to identify updated data on disorder prevalence.MethodsWe identified epidemiological studies reporting mental disorder prevalence in representative samples of children aged 18 years or younger—including a range of disorders and ages and assessing impairment (searching January 1990 through February 2021). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 41 publications
3
65
2
1
Order By: Relevance
“…Attention-deficit/hyperactivity disorder (ADHD) is the most common neurodevelopmental condition in children,1 2 and its impairing symptoms persist into adulthood in up to ~75% of childhood cases 3 4. Adult ADHD has a prevalence estimated at ~2.5%5 and is commonly comorbid with other disorders (eg, depression or anxiety)6 and with problems such as emotional dysregulation, which are often the main trigger for a referral to clinical services 6.…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is the most common neurodevelopmental condition in children,1 2 and its impairing symptoms persist into adulthood in up to ~75% of childhood cases 3 4. Adult ADHD has a prevalence estimated at ~2.5%5 and is commonly comorbid with other disorders (eg, depression or anxiety)6 and with problems such as emotional dysregulation, which are often the main trigger for a referral to clinical services 6.…”
Section: Introductionmentioning
confidence: 99%
“…Another review that included studies published between 1985 and 2012 estimated a worldwide ADHD prevalence of 3.4% (95% CI 2.6-4.5) for children and adolescents in the same age range [17]. A recently published review covering the period 2003-2020 reported a prevalence of 3.7% (95% CI 2.3-5.7%) in children and adolescents up to 18 years of age from high-income countries [18]. The variability observed in the ADHD prevalence estimates may also be influenced by the studied time period; therefore, analyzing the trends in ADHD diagnoses over time is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with adult mental health care, the mental health care of young people in Western countries has increased even more rapidly ( Olfson et al, 2014 ; Steinhausen, 2015 ). Epidemiological studies estimate that one in eight children nowadays meet criteria for a mental disorder ( Polanczyk et al, 2015 ; Barican et al, 2021 ). Parent surveys in the US found child diagnosis rates of 9.5% for ADHD, 7.4% for behavioral/conduct disorders, 7.1% for anxiety, 3.2% for depression, and 2.5% for autism spectrum disorder ( Ghandour et al, 2019 ; Zablotsky et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%